HUBUNGAN SUMBER AIR MINUM DENGAN KEJADIAN DIARE DI PROVINSI GORONTALO - Nanda Labado (Yayasan Pendidikan Medika Indonesia, 2022)
Background: Diarrhea is a health problem that often occurs in a family and can cause illness and even death. The prevalence of diarrhea based on the diagnosis of health workers for Gorontalo Province is 8.83% and the prevalence of diarrhea in children under five is 12.60%. Of the various causes due to diarrhea, one of the factors is the source of drinking water consumed. Objective: to see the relationship between drinking water sources used daily by the community with the incidence of diarrhea in Gorontalo Province. Methods: This study used a cross-sectional. The data used is secondary data for Basic Health Research (Riskesdas) in 2018 with a sample of 8,953. Data analysis was carried out univariate, bivariate, and multivariate using Binary Regression Logistics. The results of the study: diarrhea samples obtained after the data cleaning process were 8,953 in Gorontalo Province and there were 5.5% who had diarrhea. The results of the bivariate analysis showed that there was a statistically significant relationship between age, education, gender, area of ​​residence and source of drinking water with the incidence of diarrhea in Gorontalo Province. The results of the multivariate analysis showed that the most dominant variable associated with the incidence of diarrhea in this study did not exist because the p value generated in the multivariate analysis was significant at 5% alpha. Conclusion: the incidence of diarrhea is related to the source of drinking water, age, education, gender and area of ​​residence. So that health promotion in the form of communication, information and education about the management of water sources for consumption needs to be continuously promoted for efforts to improve public health Keywords: Diarrhea; Source of drinking water; Gorontalo